2023
DOI: 10.1093/humrep/dead039
|View full text |Cite
|
Sign up to set email alerts
|

Whole exome sequencing in unexplained recurrent miscarriage families identified novel pathogenic genetic causes of euploid miscarriage

Abstract: STUDY QUESTION Can whole exome sequencing (WES) followed by trio bioinformatics analysis identify novel pathogenic genetic causes of first trimester euploid miscarriage? SUMMARY ANSWER We identified genetic variants in six candidate genes that indicated plausible underlying causes of first-trimester euploid miscarriage. WHAT IS KNOWN ALREADY Previous studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…MR increase with age, and although this population is still relatively young, some age-related factors that are not related to chromosomal abnormalities may contribute to miscarriages. For example, pregnancy complications such as gestational diabetes or preeclampsia are more common in older mothers [91][92][93].…”
Section: Conclusion Our Resultsmentioning
confidence: 99%
“…MR increase with age, and although this population is still relatively young, some age-related factors that are not related to chromosomal abnormalities may contribute to miscarriages. For example, pregnancy complications such as gestational diabetes or preeclampsia are more common in older mothers [91][92][93].…”
Section: Conclusion Our Resultsmentioning
confidence: 99%
“…20,21 Exome sequencing in cases of RPL identified novel pathogenic variants in several candidate genes and their functional implications were further analyzed by gene expression knockdown using targeted siRNA in cell lines and by reduced reproductive performance in variant knock-in mice. 22,23 A new enrichment approach for candidate gene detection in unexplained RPL and implantation failure was proposed by exome sequencing, detailed bioinformatic analyses, and in silico protein structural analyses. 24 RPL with recurrent aneuploidy, compound aneuploidy, and polyploidy could be caused by pathogenic variants affecting meiotic chromosome segregation.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with single-SNP amplification and genotyping methods, the multiple-target region capture technology (MultipSeq Primer for the genotyping of SNP loci) based on next-generation sequencing technology is more cost-effective and has higher efficiency, enabling the simultaneous acquisition of a greater number of loci and genotyping results [ 32 , 36 , 37 ]. In the present study, by testing the 219 selected SNPs in 120 animals, it was found that three loci had a low amplification quality, seven loci presented the same genotype in all animals, and three loci were completely linked with other loci.…”
Section: Discussionmentioning
confidence: 99%